Evaluation of Chromium Metal in Worker Blood in Dental Laboratories and its impact on Physiological Properties - Jabbar, Alaa Taleb; Halboos, Mohanad Hazim (Journal of Science in Medicine and Life, 2025)
Indoor environmental pollution significantly impacts individual comfort and health. This environment encompasses air quality, temperature humidity lighting, ventilation and the presence of chemical. The health of workers, especially in workshops like dental laboratories, is influenced by factors such as exposure to chemical like chromium, which may volatilize in to the air or build in the bloodstream. This exposure can adversely affect liver and renal function and modify blood parameters. The present study aimed to assess chromium concentrations in the occupational settings of dentistry laboratories in Najaf governorate. We conducted the study on a sample group of sixty male and females, aged under 40 and over 40 year. The samples were categorized into two groups: the first group consisted of 40 samples from dental laboratories, while the second group included 20 samples designated as the control group. The samples were obtained from laboratory workers with working hours varying from under 6 to over 6 hours and with employment durations spanning from less than 5 to more than 10 years. These workers face an elevated risk of exposure to chromium and its related health issues. This investigation turned into carried out by way of quantifying the chromium tiers in the blood of workers and comparing it to the control sample. Certain liver enzymes (ALT and AST) and renal features (creatinine and urea) had been assessed to evaluate the effects of environmental contamination on vital organs. The outcomes indicated heightened chromium ranges inside the people' blood relative to the manage pattern, signifying exposure to abnormal concentrations of this detail. A correlation changed into identified between improved chromium ranges and negative effects on liver and kidney function, with severa people showing alterations in liver and kidney feature parameters, consisting of raised liver enzymes and markers of renal failure. It changed into determined that environmental pollution with dangerous compounds, consisting of chromium, in dentistry laboratories probably adversely influences people' health, necessitating steps to mitigate contamination and beautify health prevention programs in those settings.